2021
DOI: 10.11609/jott.6760.13.5.18110-18121
|View full text |Cite
|
Sign up to set email alerts
|

Conservation ecology of birds in Mt. Hilong-hilong, a Key Biodiversity Area on Mindanao Island, the Philippines

Abstract: The identification of key areas for conservation and protection according to science-based evidence is an important component to circumvent the negative impacts of environmental changes within geopolitical territories and across the globe.  Priority areas for biodiversity played an important role to ensure the protection of many species particularly those that are unique and threatened.  There are more than 200 Key Biodiversity Areas (KBAs) in the Philippines, yet many important research and biodiversity data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
0
1
Order By: Relevance
“…PC Hill has less vegetation and more residential buildings compared to NDU, however, results showed that it has the highest bird diversity among the urban green spaces surveyed. The results differ to the study conducted in southern Mindanao that reports the positive association of vegetation to avifaunal diversity (see Tanalgo et al 2015;Gracia et al 2021). Such observation might be due to limitations of the study such as the time of the day the bird surveys were conducted (0500-0900 h) and the limited number of study sites.…”
Section: Avifaunal Species Compositioncontrasting
confidence: 99%
“…PC Hill has less vegetation and more residential buildings compared to NDU, however, results showed that it has the highest bird diversity among the urban green spaces surveyed. The results differ to the study conducted in southern Mindanao that reports the positive association of vegetation to avifaunal diversity (see Tanalgo et al 2015;Gracia et al 2021). Such observation might be due to limitations of the study such as the time of the day the bird surveys were conducted (0500-0900 h) and the limited number of study sites.…”
Section: Avifaunal Species Compositioncontrasting
confidence: 99%